A Fragile Inheritance : Radical Stakes in Contemporary Indian Art - Mathur, Saloni (Book collections on Project MUSE., 2019)
Saloni Mathur investigates the radical work of two seminal figures--New Dehli-based critic and curator Geeta Kapur, and her husband, contemporary multimedia artist, Vivan Sundaram--to show how their approach to artistic practice and theory may inform subsequent generations and serve as a model for artistic politics in our time.